Stereotactic Ablative Radiosurgery for Locally Advanced or Recurrent Skull Base Malignancies with Prior External Beam Radiation Therapy - Xu, Karen M.; Quan, Kimmen; Clump, David A.; Ferris, Robert L.; Heron, Dwight E. (Frontiers in Oncology, 2015)
Purpose: Stereotactic ablative radiotherapy (SABR) is an attractive modality to treat malignancies invading the skull base as it can deliver a highly conformal dose with minimal toxicity. However, variation exists in the prescribed dose and fractionation. The purpose of our study is to examine the local control, survival and toxicities in SABR for the treatment of malignant skull base tumors. Methods and Materials: A total of 31 patients and 40 locally-advanced or recurrent head and neck malignancies involving the skull base treated with a common SABR regimen which delivers a radiation dose of 44 Gy in 5 fractions from January 1st, 2004 to December 31st, 2013 were retrospectively reviewed. The local control rate (LC), progression-free survival rate (PFS), overall survival rate (OS) and toxicities were reported. Results: The median follow-up time of all patients was 11.4 months (range: 0.6-67.2 months). The median tumor volume was 27 cm3 (range: 2.4-205 cm3). All patients received prior EBRT with a median radiation dose of 64 Gy (range: 24-75.6 Gy) delivered in 12 to 42 fractions. 20 patients had surgeries prior to SABR. 19 patients received chemotherapy. Specifically, 8 patients received concurrent cetuximab (ErbituxTM) with SABR. The median time-to-progression (TTP) was 3.3 months (range: 0-16.9 months). For the 29 patients (93.5%) who died, the median time from the end of first SABR to death was 10.3 months (range: 0.5-41.4 months). The estimated 1-year overall survival (OS) rate was 35%. The estimated 2-year OS rate was 12%. Treatment was well-tolerated without grade 4 or 5 treatment-related toxicities. Conclusions: SABR has been shown to achieve low toxicities in locally-advanced or recurrent, previously irradiated head and neck malignancies invading the skull base.